Energy dependence of the molecular effect in spputering - Oliva Florio, A.R.; Alonso, E. V.; Baragiola, R. A.; Ferrón, J.; Jakas, M. M. (Gordon and Breach, Science Publishets, Inc., 1979)
Fil: Cancio, David Comisión Nacional de Energía Atómica; Argentina